Pacifism and English Literature - White, R. author. aut Link
VII, 299 p.
Keywords: This timely book traces ideas of pacifism in English literature, particularly poetry. Early chapters, drawing on religious and secular traditions, provide intellectual contexts. There follows a chronological analysis of literature which rejects war and celebrates peace, from the Middle Ages to the present day.